A case study on the impact of Micromobility on Four-Arm Signalized Intersection Performance - Mehmet RIZELIOGLU (Journal of Innovative Science and Engineering)
With increasing urbanization, problems such as traffic congestion and environmental pollution have become more pronounced. Alternative modes of transportation such as micromobility (bicycles, e-scooters, e-bikes, segways) have the potential to reduce these problems. This study analyzes the effects of micromobility on the performance of an intersection using a simulation-based approach. A four-arm signalized intersection in Nilüfer, Bursa, is taken as a model, and the impact of micromobility on intersection performance is evaluated in terms of "average vehicle speed", "queue delay", and "vehicle travel time" performance indicators. In the study, the inclusion of micromobility at low levels (2.5% and 5%) improves intersection performance, while at higher levels (7.5% and 10%) this improvement is reversed, resulting in longer travel times and lower speeds. Signal modification has shown an improvement in the performance of the intersection. However, these results suggest the need for special signaling studies for micromobility vehicles at intersections. The study provides important findings for transportation management and policy makers in micromobility planning.